2016
DOI: 10.1093/jae/ejw003
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Aid Effects on Tax Revenues: Accounting for Government Stability in WAEMU Countries

Abstract: We examine the heterogeneous effects due to government stability of foreign aid on tax revenues in the West African Economic and Monetary Union countries over the period 1986-2010. We show that the tax effects of aid are gradual and varying across countries according to the level of government stability. The Panel Smooth Threshold Regressions indicate that at low levels of government stability, aid negatively affects tax performances. At high levels, it encourages tax collection. Consequently, we provide estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 52 publications
(38 reference statements)
1
39
0
Order By: Relevance
“…Morrissey (2015) indicates three conclusions on the effects of foreign aid; "aid finances government spending; the extent to which aid is fungible is over-stated and even where it is fungible this does not appear to make the aid less effective; and there is no systematic effect of aid on tax effort" (Morrissey 2015, pp.98). Yohou et al (2016) and Clist (2016) largely support this assertion. The extent of the impact of foreign aid on the countries that receive them are often influenced by how their governments 'behave' since such aid goes through the public sector (McGillivray & Morrissey 2000).…”
Section: Determinants Of the Growth Of Government Spending -A Brief Smentioning
confidence: 67%
“…Morrissey (2015) indicates three conclusions on the effects of foreign aid; "aid finances government spending; the extent to which aid is fungible is over-stated and even where it is fungible this does not appear to make the aid less effective; and there is no systematic effect of aid on tax effort" (Morrissey 2015, pp.98). Yohou et al (2016) and Clist (2016) largely support this assertion. The extent of the impact of foreign aid on the countries that receive them are often influenced by how their governments 'behave' since such aid goes through the public sector (McGillivray & Morrissey 2000).…”
Section: Determinants Of the Growth Of Government Spending -A Brief Smentioning
confidence: 67%
“…At the same time, Ouattara (); Mavrotas and Ouattara (); Morrissey, Prichard, and Torrance (), have found a statistically nil effect of development aid on tax revenue. Yohou, Goujon, Michaël, and Ouattara () have reported that the effect of development aid on tax revenue performance is conditional on government stability: while aid directly lowers tax revenue performance, it enhances it for higher levels of government stability. Gnangnon and Brun () have examined the sustainability of development aid on non‐resource tax revenue performance of recipient countries and obtained evidence that such sustainability is dependent on countries' development level.…”
Section: Model Specificationmentioning
confidence: 99%
“…More recently, Yohou et al, (2016) find evidence -over a set of West African Countries-, that the impact of aid on tax revenue is gradual and varies across countries, depending on the level of government stability: aid appears to directly reduce tax revenue, but improves the latter for higher levels of government stability.…”
Section: Interaction Between Development Aid and Government Public Rementioning
confidence: 99%
“…The link between domestic public finance and other financing flows for development, including international public finance inflows (ODA) and international private inflows has been explored in the economic development literature (see for e.g., Grubert and Mutti, 1991;Brun et al, 2011a;Selaya and Sunesen, 2012;Morrissey, 2015;Yohou et al, 2016). In the meantime, many studies have been carried out on the effect of international trade openness on these different types of financing for development flows, notably government public revenue, development aid, and foreign investment (see for e.g., Dudley and Montmarquette, 1976;Neumayer, 2003a;Nashashibi and Bazoni, 1994;Alesina and Dollar, 2000;Khattry and Rao, 2002;Baunsgaard and Keen, 2010).…”
Section: Introductionmentioning
confidence: 99%